2012
DOI: 10.1007/s00442-011-2242-3
|View full text |Cite
|
Sign up to set email alerts
|

Ozone exposure causes a decoupling of conductance and photosynthesis: implications for the Ball-Berry stomatal conductance model

Abstract: Industrialization has significantly altered atmospheric chemistry by increasing concentrations of chemicals such as nitrogen oxides (NO( x )) and volatile organic carbon, which react in the presence of sunlight to produce tropospheric ozone (O(3)). Ozone is a powerful oxidant that causes both visual and physiological damage to plants, impairing the ability of the plant to control processes like photosynthesis and transpiration. Damage to photosynthesis and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 50 publications
4
71
1
1
Order By: Relevance
“…The O 3 exposure induces an uncoupling of photosynthesis and stomatal conductance, as previously observed in three native tree species from China (Ailanthus altissima, Fraxinus chinensis and Platanus orientalis) [35]. Lombardozzi et al [19] reported that the typical coupling of stomatal conductance and photosynthesis does not always hold under high O 3 conditions, because O 3 can directly affect the function of stomatal cells so that g s no longer responds dynamically to changes in C i and the rate of carboxylation due to enzyme and membrane damage. Unchanged g s with increased C i in the second growing season, as observed in this study, indicated that the decrease in photosynthesis was independent of g s [15,36].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The O 3 exposure induces an uncoupling of photosynthesis and stomatal conductance, as previously observed in three native tree species from China (Ailanthus altissima, Fraxinus chinensis and Platanus orientalis) [35]. Lombardozzi et al [19] reported that the typical coupling of stomatal conductance and photosynthesis does not always hold under high O 3 conditions, because O 3 can directly affect the function of stomatal cells so that g s no longer responds dynamically to changes in C i and the rate of carboxylation due to enzyme and membrane damage. Unchanged g s with increased C i in the second growing season, as observed in this study, indicated that the decrease in photosynthesis was independent of g s [15,36].…”
Section: Discussionmentioning
confidence: 52%
“…Reductions in A sat have been attributed to decreases in primary carboxylation enzyme Rubisco transcript levels, antioxidant contents and enzyme activity rather than changes in g s [17,18]. A recent study suggests that elevated O 3 induces faster rates of change in photosynthesis rate compared to g s because of the significant decrease in the maximum activity of Rubisco (V c,max ) and maximum electron transport rate (J max ), i.e., O 3 reduces the biochemical capacity to fix CO 2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone has a negative impact on crop production by reducing gas exchange and inflicting phytotoxic damage on plant tissues (Lombardozzi et al, 2012;Sitch et al, 2007;Wilkinson et al, 2011). The crop-specific relationships between surface ozone concentration and crop yield loss have been established using several exposure metrics.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido se ha sugerido que existe una estrecha correlación entre la conductancia y la fotosíntesis en un amplio rango de condiciones ambientales, ya que los estomas responden a los cambios ambientales como la radiación y el déficit de presión de vapor (Lombardozzi et al, 2012).…”
Section: Conductancia Estomática Y Relación Con Variables Ambientalesunclassified